Flourishing in Student Veterans With and Without Service-Connected Disability: Psychometric Validation of the Flourishing Scale and Exploration of Its Relationships With Personality and Disability. (October 2019) - Umucu, Emre; Grenawalt, Teresa Ann; Reyes, Antonio; Tansey, Timothy; Brooks, Jessica; Lee, Beatrice; Gleason, Carey; Chan, Fong
Veterans are an increasing population in postsecondary education. Many student veterans have disabilities affecting their well-being and success in college. This study aims to add to current knowledge on well-being by exploring the relationship between flourishing, personality traits, and service-connected disability among student veterans. First, we set out to psychometrically validate the Flourishing Scale (FS) for student veterans. Second, we evaluated the association of the Big-Five personality traits and flourishing. Finally, we evaluated the differences in flourishing among student veterans with and without service-connected disabilities. Two hundred five student veterans were recruited for the current study. A random split-half approach was adopted to perform an exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Subsequent to conducting the EFA and CFA, a hierarchical multiple regression analysis was performed to investigate the relationships between flourishing and Big-Five personality traits. Finally, an independent-samples t test was conducted to compare the flourishing scores of student veterans with and without a service-connected disability. Findings indicated FS is a reliable and valid scale that could be used to measure flourishing in student veterans. Detailed findings and their implications for rehabilitation counseling are provided.